Digitalisation of Border Control through Autogate and the Emerging Configuration of Immigration System Resilience in Indonesia - Besse Hartati; Sunarto; Pandji Sukmana; T. Herry Rachmatsyah (International Journal of Social Science and Religion (IJSSR), 2026)
This article examines Indonesia’s autogate policy not only as a digital service innovation, but as a component of immigration system resilience. Drawing on policy implementation theory by Edwards III, Sabatier & Mazmanian, e-government literature on the design reality gap, system resilience thinking, and the information security CIA triad, the study analyses how autogate is designed, regulated, and operated at major international airports. Using a qualitative descriptive approach based on documentary and literature review, it maps legal foundations, organizational arrangements, and technical narratives surrounding automated border control. The findings show that autogate has improved processing times, standardized procedures, and strengthened traceability through digital logs, thereby supporting efficiency, accountability, and internal control. However, recurrent system downtime, biometric errors, incomplete system integration, and heavy dependence on infrastructure reveal significant vulnerabilities in confidentiality, integrity, and availability of data. Fragmented governance across immigration, airport operators, cybersecurity, and communications authorities reinforces a design–reality gap, limiting coordination, local ownership, and adaptive capacity. The article concludes that autogate currently functions as a double-edged innovation, symbolizing digital modernization while only partially reinforcing immigration system resilience. It recommends clearer mandates, stronger cross-sector coordination, improved data governance, and investment in human resources and risk-based oversight to align automated border control with a more robust, rights-sensitive model of digital immigration governance.